Umbilical Dermoid Cyst: A Rare Case - Akıncı, Ozan; Türker, Cansu; Ertürk, Murat Süphan; Yüceyar, Necip Serdar (Cerrahpaşa Medical Journal, 2020)
Dermoid cysts, a majority of which arise from the ovaries and testicles, can occur in any part of the body in which embryonic elements fuse together. The epithelial-lined cystic cavity of dermoid cysts encloses skin appendages such as hair, hair follicles, sebaceous, and sweat glands. In the literature, very few studies have reported umbilicus-located dermoid cysts. Dermoid cysts generally present as painless slow-growing well-circumscribed lesions. A standard treatment for dermoid cysts, whose definitive diagnosis can be made through histopathological examinations, is surgical excision of the lesion. This study reports a rare case of an umbilicus-located dermoid cyst detected through ultrasound, wherein a dermoid cyst was diagnosed in histopathological evaluation after surgical excision. Cite this article as: Akıncı O, Türker C, Ertürk MS, Yüceyar NS. Umbilical Dermoid Cyst: A Rare Case. Cerrahpasa Med J 2020; 44(1): 51-53.